Comparable luminescence investigation of the La1-xEuxVO4 solid solutions synthesized by two different methods - Chukova, O. V.; Nedilko, S. G.; Scherbatskii, V.; Nedilko, S. A.; Voytenko, T. (Видавництво Львівської політехніки, 2012)
Luminescence properties of the series of the La1-xEuxVO4 solid solutions were investigated. The samples were synthesized by the solid state and co-precipitation methods. Luminescence spectra of the investigated samples consist of weak wide non-structural band of the matrix emission and narrow spectral lines caused by inner f-f electron transitions in the impurity Eu3+ ions. Dependences of the structure, peak positions and intensity of luminescence on the composition, samples temperature and excitation wavelengths were studied. Differences between luminescence characteristics of series of samples obtained by two different methods are considered.
Keywords: luminescence; vanadate; Eu3+ ions